Pengaruh Growth Mindset Dan Motivasi Belajar Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Ekonomi (Survei di SMA Negeri 3 Ciamis Tahun Ajaran 2024/2025) - Ramadhanti, Adinda Nur; Widyaningrum, Bakti; Solihat, Ai Nur (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This study is motivated by the low student learning outcomes in economics subjects triggered by the lack of student enthusiasm for economic subject matter. Students' lack of enthusiasm for economic subjects has an impact on the low active participation of students in the learning process, reduces understanding of economic subject matter and ultimately leads to unsatisfactory learning outcomes in economic subjects. One of the efforts to overcome these problems is by applying the concept of growth mindset and learning motivation in the learning process in economics subjects. This study aims to determine the effect of growth mindset and learning motivation on learning outcomes. The research method used is using survey method with explanatory design. The population in this study were XII F1-F3 class students at SMA Negeri 3 Ciamis who took economics subjects totaling 102 people. The sampling technique used saturated samples. The data collection technique used in this study was a questionnaire and the data analysis technique used was multiple linear regression analysis. The results of this study indicate that there is a positive and significant influence between growth mindset on learning outcomes with a significance value of 0.004, there is a positive and significant influence between learning motivation on learning outcomes with a significant value of 0.000, and there is a positive and significant influence between growth mindset and learning motivation on learning outcomes with a significance value of 0.000.